STRATEGI PEMBELAJARAN TEMATIK MELALUI PENDEKATAN INTERAKTIF DI MADRASAH IBTIDAIYAH NEGERI 1 KUBU RAYA - Salito (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Learning strategy is the process of selecting and arranging learning activities in a learning unit such as the sequence, nature of the material, scope of material, methods and media that are most appropriate to achieve learning competencies. It is necessary to choose the right learning strategy in thematic learning, especially in grade IV children. Choosing the right learning strategy can make it easier for students to achieve competencies or learning objectives. The method used by Qualitative is discriminative with observational data analysis techniques, interviews and documentation, with two teachers consisting of class A, the number of students is 30 people and class B is 31 students. The results showed that teachers use learning strategies through an interactive approach. The research was conducted through observation by interviewing the Head of Madsarah and Homeroom Class IV MIN 1 Kubu Raya. The results of the study, teachers use an interactive approach with the aim of stimulating children to think creatively. The inhibiting factor is in children who are not good at socializing, therefore he is reluctant to respond to questions and ask questions so that teachers must pay more attention which will make children more confident.